Intrathecal Immunoglobulin M Synthesis is an Independent Biomarker for Higher Disease Activity and Severity in Multiple Sclerosis. Issue 3 (22nd June 2021) - Oechtering, Johanna; Schaedelin, Sabine; Benkert, Pascal; Müller, Stefanie; Achtnichts, Lutz; Vehoff, Jochen; Disanto, Giulio; Findling, Oliver; Fischer‐Barnicol, Bettina; Orleth, Annette; Chan, Andrew; Pot, Caroline; et al.
Abstract : Objective: We aimed to determine in relapsing multiple sclerosis (MS) whether intrathecal synthesis of immunoglobulin (Ig) M and IgG is associated with outcomes reflecting inflammatory activity and chronic worsening. Methods: We compared cerebrospinal fluid analysis, clinical and magnetic resonance imaging data, and serum neurofilament light chain (sNfL) levels at baseline and follow‐up in 530 patients with relapsing MS. Patients were categorized by the presence of oligoclonal IgG bands (OCGB) and intrathecal synthesis of IgG and IgM (intrathecal fraction [IF]: IgGIF and IgMIF ). Relationships with the time to first relapse, sNfL concentrations, T2‐weighted (T2w) lesions, MS Severity Score (MSSS), and time to initiation of high‐efficacy therapy were analyzed in covariate‐adjusted statistical models. Results: By categorical analysis, in patients with IgMIF the median time to first relapse was 28 months shorter and MSSS on average higher by 1.11 steps compared with patients without intrathecal immunoglobulin synthesis. Moreover, patients with IgMIF had higher sNfL concentrations, more new/enlarging T2w lesions, and higher total T2w lesion counts (all p  ≤ 0.01). These associations were absent or equally smaller in patients who were positive for only OCGB or OCGB/IgGIF . Furthermore, quantitative analyses revealed that in patients with IgMIF  ≥ median, the time to first relapse and to initiation of high‐efficacy therapy was shorter by 32 and by 203 months, respectively (both p  < 0.01), in comparison to patients with IgMIF  < median. Dose‐dependent associations were also found for IgMIF but not for IgGIF with magnetic resonance imaging‐defined disease activity and sNfL. Interpretation: This large study supports the value of intrathecal IgM synthesis as an independent biomarker of disease activity and severity in relapsing MS. ANN NEUROL 2021;90:477–489